Increasing The Competitiveness of Msmes In Parongpong District Through The Use of E-Commerce and Branding Strategies - Wahyu Wahyu Rafdinal; Lusianus Kusdibyo; Nugroho Hardiyanto; Maya Setiawardani; Mohammad Rizal Gaffar; Abdul Malik Sayuti; Tangguh Dwi Pramono; Ivon Sandya Sari Putri (International Journal Of Community Service, 2024)
The purpose of this program is to develop modules and training modules developed to improve the performance of MSMEs in Parongpong District. Identification of partner problems is carried out through document studies, interviews, and questionnaire dissemination. Based on the analysis of partner problems, there are several problems that cause MSMEs in Parongpong District to not utilize e-commerce media as their marketing media, namely: (1) Do not have knowledge and skills in using e-commerce; (2) Products that are not ready to be marketed in terms of branding, packaging that is not yet attractive, and product durability; (3) Do not understand how to use SEO (search engine optimization) in increasing product visibility in e-commerce. If these three main problems can be solved, it is expected that MSMEs can compete on various e-commerce platforms that exist today. The solution provided to partners is to develop the necessary modules and provide training for; (1) improve skills in using several e-commerce platforms; (2) increase knowledge and ability in creating branding, making attractive packaging, and preserving industry-standard products; (3) improve knowledge and skills in the use of SEO (search engine optimization). The impact resulting from this training is that MSMEs gain competencies to increase the competitiveness of marketed products. The supporting capacity provided includes the availability of (1) MSME product branding materials; (2) product packaging materials; (3) marketing materials; and (4) SEO utilization materials.